ANALISIS NARATIF PADA KONTEN FILOSOFI HINDU PADA TIGA RELIEF CANDI KIDAL DI AKUN YOUTUBE ASISI CHANNEL - Toni, Ahmad (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2022)
This research is a narrative analysis research on YouTube Social media by analyzing the content on the Asisi Channel. The method used in this research is narrative analysis. The results of the study show that there are two narratives related to the narrative of the three sacred areas in the temple, namely: the Jaba Mandala, the madya mandala, and Utama mandala. Second, the narrative about the mythological Garuda as a warrior who feed his mother, Dewi Winata from the slavery of the Naga (Dewi Kadru) which contains Hindu philosophical values and is applied in the Indonesia government system.